Monkey and Elephant and a secret birthday surprise - Schaefer, Carole Lexa; Bernstein, Galia (Somerville, Massachusetts Candlewick Press, 2015)
When monkey confides to elephant that today is his birthday, elephant decides to turn Clever Rat's get together into a surprise birthday party for his friend
Keywords: Birthday parties -- Juvenile fiction; Elephants -- Juvenile fiction; Friendship -- Juvenile fiction; Monkeys -- Juvenile fiction; Surprise birthday parties -- Juvenile fiction; Birthday parties -- Fiction; Elephants -- Fiction; Friendship -- Fiction; Monkeys -- Fiction; Surprise birthday parties -- Fiction; Elephants -- Juvenile fiction; Birthday parties; Birthday parties; Birthday parties; Elephants; Elephants; Elephants; Friendship; Friendship; Friendship; Monkeys; Monkeys; Monkeys; Surprise birthday parties; Surprise birthday parties; Surprise birthday parties; Fiction; Fiction; Fiction; Juvenile works; Juvenile works; Juvenile works